2021
DOI: 10.52152/spr/2021.118
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the First COVID-19 Case in Kosovo and Management of the Pandemic

Abstract: In the view of the first anniversary of COVID-19, this article focuses on the first COVID-19 case in Kosovo, a 22-year-old woman who came from abroad. COVID-19 has become a major threat to the health of the youngest population in Europe. We also considered the efficacy of restrictive measures, such as lockdowns, in Kosovo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The etiology of RSA is complex and diverse, and in addition to genetic, anatomical abnormalities, endocrine disorders, infections, autoimmunity, sperm quality, lifestyle, psychosomatic, and environmental factors, the etiology of 50%–75% of RSA is still unknown [ 5 ]. The literature [ 6 ] shows that a significant proportion of recurrent spontaneous abortions are associated with immune factors. The HLA gene system is the most complex polymorphic system known in humans, and it has an important influence on the way the human immune system is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of RSA is complex and diverse, and in addition to genetic, anatomical abnormalities, endocrine disorders, infections, autoimmunity, sperm quality, lifestyle, psychosomatic, and environmental factors, the etiology of 50%–75% of RSA is still unknown [ 5 ]. The literature [ 6 ] shows that a significant proportion of recurrent spontaneous abortions are associated with immune factors. The HLA gene system is the most complex polymorphic system known in humans, and it has an important influence on the way the human immune system is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complex pathogenesis of DN, there is no curative therapy, and most patients require renal replacement therapy [ 7 ]. Diabetic nephropathy is one of the most common microvascular complications, and the lung is a relatively microvascular and collagen-rich organ and therefore vulnerable to diabetic microangiopathy and histone nonglycosylation [ 2 , 8 ]. Alterations in microvascular ultrastructure regulate the thickening of the alveolar capillary endothelial cell matrix, which in turn affects pulmonary ventilation and pulmonary diffusion function [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown [7] that drug therapy can repair damaged cornea and maintain structural and functional stability of the eye. Sodium hyaluronate eye drops are used as an external medicine for eye diseases, mainly composed of sodium hyaluronate; when used as a substitute for artificial tears, it can relieve dry eyes and play a lubricant effect; calf blood-deproteinizing extract eye gel mainly consists of 20% calf blood-deproteinizing extract and part of free amino acids, which can improve eye cell function [8,9]. e efficacy of these two drugs is slow, and the clinical efficacy of combined therapy is limited for patients with dry eye disease.…”
Section: Introductionmentioning
confidence: 99%